Synergetic effect of BN for the electrical conductivity of CNT/PAN composite fiber - Kim, Heejin; Jeon, Dae-Young; Jang, Se Gyu; Lee, Min Wook (대한기계학회, 2022)
Carbon nanotube (CNT) fillers in composite materials improve electrical conductivity, thermal stability, and mechanical properties. Boron nitride (BN) is an insulating material that is also thermally stable. Therefore, CNT and hexagonal boron nitride (hBN) fillers have been used to obtain composite materials' high electrical conductivity. In this study, CNT-hBN/polyacrylonitrile (PAN) fibers were spun using simple wet-spinning and the effect of hBN on the electrical conductivity of the CNT-hBN/PAN composite was investigated. Contrary to predictions, as the content of the insulating material, BN, increased up to 15 wt%, the electrical resistance of the composite fiber decreased.